Spatial-temporal dynamics and associated driving forces of urban ecological land: A case study in Shenzhen City, China. (February 2017) - Peng, Jian; Zhao, Mingyue; Guo, Xiaonan; Pan, Yajing; Liu, Yanxu
Abstract: Ecological land is an important component of urban ecosystems. Detecting the change of urban ecological land and its driving forces will offer scientific basis for the optimization of urban landscape patterns. The rapid urbanization in Shenzhen City has brought the serious conflicts between socio-economic development and ecological protection. In this study, we characterized ecological land dynamics in Shenzhen City and quantified the driving forces using multivariate logistic regression, and subsequently mapped the transition probability of ecological land. The results showed that in Shenzhen City, urban ecological land had changed dramatically during 1990–2010 in terms of its quantity, quality, and spatial distribution. Land use change matrix between ecological and non-ecological land showed that the area of ecological land decreased more fast during 1990–2000, compared with that during 2000–2010. There was a decrease in area equivalents calculated by the adjustment coefficient of ecosystem services, although the quality per unit was improved. Furthermore, the gravity center of ecological land gradually moved to the southeast. The driving force analysis suggested that the slope, the minimum distance to construction land, and the growth rate of construction land were the vital factors determining the change of urban ecological land. Finally, the transition probability mapping showed that the water body, wetland and grassland near the city center had a higher transition probability to construction land. This study illustrated the change characteristics of urban ecological land, as a result of rapid urbanization. The transition probability can serve as the basis for decision making on constructing urban landscape ecological security pattern. Highlights: The quantity, quality and distribution change of ecological land was detected. The slope and minimum distance to construction land hinder ecological land change. The growth rate of construction land leads to ecological land change. The transition probability from ecological land to construction land was mapped.